THE EFFECTS OF PROFESSIONAL COMPETENCE, WORK DISCIPLINE, AND WORK MOTIVATION ON THE PERFORMANCE OF MADRASAH ALIYAH NEGERI TEACHERS IN THE RIAU ISLANDS PROVINCE - Erlina Gusnita; Ahmad Syukri; Lukman Hakim (As-Sulthan Journal of Education, 2026)
This study examines the effects of professional competence, work discipline, and work motivation on the performance of teachers at Madrasah Aliyah Negeri in the Riau Islands Province. The scope of this research focuses on analysing both the partial and simultaneous influence of these three variables in order to provide a comprehensive understanding of key determinants of teacher performance in Islamic secondary schools within an archipelagic context. The main objective of the study is to identify the extent to which professional competence, work discipline, and work motivation contribute to improving teacher performance. This study employed a quantitative research design with a correlational and explanatory approach. The population consisted of all teachers of Madrasah Aliyah Negeri in the Riau Islands Province, and the sample was selected using proportional sampling techniques. Data were collected through structured questionnaires and analysed using multiple linear regression analysis. The results indicate that professional competence, work discipline, and work motivation each have a positive and significant effect on teacher performance. Furthermore, the simultaneous analysis shows that these three variables jointly explain a substantial proportion of the variance in teacher performance. The study concludes that integrated strategies to enhance competence, strengthen discipline, and increase motivation are essential for improving teacher performance and educational quality.